Exact Relationship between Black Phosphorus Thickness and Behaviors of Field-Effect Transistors - Liefeng Feng; Kaijin Liu; Miaoyu Wang (Applied Sciences, 2023)
As a two-dimensional (2D) semiconductor material with excellent optoelectronic properties, black phosphorus (BP) has attracted widespread attention. It was found that the energy band structure of BP crystal changes with its thickness if BP is thin. To explore the accurate effects of the BP thicknesses on devices, BP-FETs with different BP thickness (50 nm, 40 nm, 30 nm, 20 nm, and 6 nm) as the channel material were fabricated by mechanical exfoliation technique. The output characteristics and transfer characteristics of the BP-FETs were analyzed in detail. The source–drain current (Ids) of devices is directly related to the BP thickness. The larger the BP thickness, the larger the Ids obtained under the same gate voltage modulation, but the electric field modulation effect decreases. Especially, the correlation between Ids and BP thickness can be described by a semi-empirical formula, which predicts that only when the BP thickness is less than 21.7 nm, the band structure of BP will be significantly affected by the thickness. The mobility of the carrier increases with the increasing of the BP thickness; for BP thickness of 6 nm, 20 nm, 30 nm, 40 nm, and 50 nm, the mobility is about 52.5 cm2/Vs, 187.5 cm2/Vs, 214.4 cm2/Vs, 252.5 cm2/Vs, and 336.4 cm2/Vs. Finally, the 50 nm BP in FET was etched to 30 nm using plasma etching technology to further verify the above experimental results. It also confirmed that plasma etching methods tend to introduce structural damage and impurity elements, which in turn has an impact on the output characteristics of the device.